Parliament in British politics - Norton, Philip (Houndmills, Basingstoke, Hampshire : Palgrave Macmillan, 2013)
'This fully revised new edition includes expanded coverage of Parliament's relationship with the courts, devolved assemblies and the European Union. Distinctively, the book goes beyond the usual focus of Parliament-Government relations to encompass policy-makers beyond Whitehall and Parliament's broader relationship with citizens'--
Machine generated contents note: -- Parliament in Perspective -- The Development of Parliament -- PART I: PARLIAMENT AND GOVERNMENT -- Recruiting Ministers -- The Making of Public Policy -- Legislation -- The Administration of Government -- PART II: BEYOND WHITEHALL -- Parliament and the European Union -- Parliament and Devolution -- Parliament and the Courts -- PART III: PARLIAMENT AND THE PEOPLE -- Representing the People -- The Voice of the Constituents -- Speaking for Different Interests -- Reaching the Public -- Conclusion: Parliamentary Reform.
Includes bibliographical references : pages 299-321 and index.
Keywords: United Kingdom -- Politics and government -- 21st century